Virtual reality for Treatment of Amblyopia in adults: Doi: 10.36351/pjo.v38i3.1398 - Rebecca; Junejo, Murtaza Sameen; Tahir, Muhammad; Shaikh, Fahad Feroz; Laghari, Nazir Ashraf (Pakistan Journal of Ophthalmology, 2022)
Purpose: To observe efficacy of Virtual reality technology as a potential treatment for improving vision in anisometropic amblyopia without the need of occlusion or penalization. Study design: Experimental case series Place and Duration of study: Isra University Hospital, Hyderabad, from Nov 2020 to Oct 2021. Methods: Patients (more than 12 years of age), with Anisometropic amblyopia, were included in this study. Patients with history of strabismus, cataract or any active ocular surface disease were excluded. Unaided visual acuity, pinhole test and best-corrected visual acuity were recorded, before and after treatment. LogMAR chart was used for this purpose. Crowding phenomenon was also checked. Anterior segment and posterior segment examination was done to rule out any organic cause of disease. A head mounted device-virtual reality glasses (HMD-VR) was used 40 min daily for 03 months to improve visual acuity. All the data was recorded on a proforma. SPSS version 22.0 was used for data analysis and P-value of <0.05 was considered significant. Result: Mean age of the patients was 24.2 years (range 14-35 years). Out of 14 registered cases, 08 (57.1 %) patients showed improvement after 08 weeks of initiation of treatment with VR glasses. Two (14.3%) patients showed improvement after 12 weeks and two showed no improvement, while two (14.3%) patients lost to follow up. After applying paired t test the value of p was < 0.001, which was statistically significant. Conclusion: This HMD VR glasses seems to be an effective option for treatment in adults with anisometropic amblyopia.